Association of screen exposure with psychosocial problems in primary school students - Hu, Zedan; Bi, Sitong; Wang, Wei; Liu, Chunjing; Li, Lihua (Frontiers in Pediatrics, 2023)
Introduction This study aimed to investigate the current status of screen exposure and the factors related to screen exposure in primary school students and explore the relationship between screen exposure and psychosocial problems, which may provide evidence for the scientific use of electronic products and psychological interventions used in these children. Methods The parents of 811 primary school students aged 6–12 years received a questionnaire survey in Beijing between January 13 and January 16, 2022. The demographic data and daily screen exposure time were collected, and the Strengths and Difficulties Questionnaire (SDQ) about their children was administered online. Results In 793 students, the average daily screen exposure of <2 h and ≥2 h was noted in 75.0% and 25% of patients, respectively. The mobile phone was the main medium for screen exposure (40.9%). The family’s economic level, parental relationship, and main supervisor were related to screen exposure time (χ2 = 44.8,14.5 and 12.4, P < 0.05). A low family economic level with a monthly income not meeting the basic living needs, poor parental relationship, and an elderly person responsible for supervision were related to increased screen exposure time. The abnormal emotional and behavioral symptoms, conduct problems, hyperactivity inattention, peer communication, prosocial behaviors, and a total difficulties score were found in 11.6%, 9.8%, 15.3%, 22.1%, 6.8%, and 13.4% of children, respectively. Excessive screen exposure was related to peer interaction and prosocial behaviors (χ2 = 12.18 and 7.76, P < 0.05). The children with excessive screen exposure were more likely to have abnormal peer interaction (χ2 = 12.09, P = 0.001) and prosocial behaviors (χ2 = 7.76, P = 0.005). Excessive screen exposure was a risk factor for peer interaction problems (P < 0.05). Discussion In conclusion, the detection rate of excessive screen exposure is higher in primary school students, which is related to the family’s economic level, parental relationship, and main supervisor. Excessive screen exposure is harmful to the psychosocial health of these children, which is characterized by abnormal peer intercommunion and prosocial behaviors. More attention should be paid to screen exposure time in primary school students.